Membangun Karakter Remaja Yang Positif Dengan Edukasi Billying Pada Remaja - Bayu Dwisetyo; Agust A. Laya; Suryani Hamid; Sintia Ismail; Alvandi Poluan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Bullying is an aggressive act committed by an individual or group with a high level of social recognition or power against an individual or group with a low level of social recognition or power. Bullying aggressive behaviour is criminal behaviour and the victim feels helpless, mentally depressed. In minimising victims of bullying and reducing perpetrators of bullying, the implementation of community service is carried out through education of the community, especially adolescents, so that they know that this behaviour is a crime, so that it can reduce the number of bullying in society. The purpose of this service is to increase public awareness of the negative impact of bullying, so that it will form a positive attitude and socialisation among others. The method of service carried out applies lecture, discussion and questioning methods to the community and adolescents in the Depok area, West Java. The results of community service through bullying prevention education are increasing awareness to the community, especially students or adolescents, to prevent bullying behaviour, protect victims by reporting perpetrators, instill an attitude of social care among friends both in the school environment and the community